THE IMPACT OF SCREEN TIME ON THE GROWTH AND DEVELOPMENT OF TODDLER IN THE CITY OF SURABAYA - Della Firsty Apskania (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
This research aims to determine the impact of screen time on the development of toddlers in the city of Surabaya. After distributing questionnaires to residents of the city of Surabaya who have children under five, 110 respondents were obtained who filled out questionnaires to become supporting data for this research. The results of this study show that screen time given to toddlers with a period of less than 1 hour per day will result in better sleep quality, because children will get enough sleep for at least 10 hours per day consisting of naps and nighttime sleep. Apart from that, it will produce more toddler play activities so that toddlers will prefer playing with their friends rather than having to play alone with gadgets. Giving children less than one hour of screen time per day will result in better toddler socialization activities. Toddlers will adapt more easily to their new environment and be more confident when they meet new people because their social psychology development is very good. Apart from that, toddlers have better eye and hand coordination, meaning that children's fine motor and gross motor development is also very good, as well as toddlers' better communication skills. Toddlers can answer their parents' calls more quickly and answer more quickly when their parents ask. Toddlers who can communicate both ways with their parents and other people indicate that their verbal and logical skills are very well developed.